Performance Evaluation of ADS 1256 for Geoelectric Data Acquisition System: Laboratory Scale Comparative Study - Pratama, Yudha Agung; Suharsono, Suharsono (Himpunan Ahli Geofisika Indonesia (HAGI), 2025)
The need of flexible and affordable geoelectric data acquisition systems is growing, particularly for research and educational purposes. This study aimed to evaluate the performance of a resistance measurement system based on the ADS1256 high-precision ADC module on a laboratory scale. Initial testing was conducted on a laboratory scale using various resistance values. The best accuracy was found in the medium to high resistance range R1 (subsurface target) (>10 Ω); at low resistance, the accuracy value decreased dramatically. A relative error (ε) reading of - 6.7% occured at low values of R1. The condition of the resistance R2 (surface) affected the stability of the ADS 1256 system reading. Based on the standard deviation value there was an indication of nonlinearity in the readings, particularly in the voltage readings. The current measurements produced relatively stable readings. There was an increase in the fluctuation of readings, especially at low surface medium (R2). Overall, the ADS1256 system demonstrated promising potential as a low-cost alternative for resistance measurement, particularly effective in the medium to high resistance range. Comprehensive data across all R1 and R2 variations require additional calibration and enhanced circuit stability to better align with reference values